Hydrocephallus in the Department of Child Health, School of Medicine University of North Sumatera Dr. Pirngadi Hospital, Medan - Yahya G. Lubis; T. Razif; Manihar D. Marbun; Bistok Saing (Indonesian Pediatric Society, 1993)
A retrospective study 10 find out the incidence of hydrocephalus in the Paediatric Neurology Subdivision Department of Child Health, School of Medicine, University of North Sumatera/Dr. Pirngadi Hospital Medan, was carried out in the period of 1986- 1989. The number, age groups, causes and treatment were reviewed. The cases consisted of 45 children; 28 males (68.2%) and 17 females (27.8%). Most of the patients (34 = 75.5%) were found in the age group of 1 year or younger and the rest (11 = 24.5%) were tn the age group of more than I year. The youngest was 2 days old and the oldest was 5 years and 6 months old; 33 cases were congenital, 5 cases were acquired and 7 cases were unknown causes. Conservative treatment were introduced to almost all cases, and four cases had ventricular peritoneal shunt.